Comparative study of low-temperature PECVD Of amorphous silicon using mono-, di-, trisilane and cyclohexasilane - Pokhodnya, K.; Sandstrom, J.; Olson, C.; Xuliang Dai; Boudjouk, P.R.; Schulz, D.L. (2009 34th IEEE Photovoltaic Specialists Conference (PVSC), 2009)
The hydrogenated amorphous silicon a-Si:H films were grown by plasma-enhanced chemical vapor deposition (PECVD) using liquid cyclohexasilane Si 6 H 12 (CHS). The growth rate of a-Si:H was studied as a function of substrate temperatures in the range of 30 °C<T<450°C using deposition conditions that were optimized for monosilane SiH 4 . The same parameters were used for a- Si:H films grown using disilane (Si 2 H 6 ) and trisilane (Si 3 H 8 ) precursors. It was found that the a-Si:H film growth rate of CHS is lower with respect to those of mono-, di- and trisilane in an Ar plasma. Addition of ~10% of H 2 dramatically increases the deposition rate for CHS-based films about 700% to 8 ¿/sec. The as-deposited films were characterized by FTIR and Raman spectroscopy to probe the hydrogen content and local bonding environment. It was found that the films grown using Ar/H 2 mixtures as carrier gas have a reduced hydrogen content relative to polysilane fragments indicating higher quality amorphous silicon.